A Study on OBE Teaching Design for College English Guided by “Telling China’s Stories Well” - Ye, Shuang (Journal of Educational Research and Policies, 2026)
Guided by the requirement of telling China’s stories well, this paper constructs an integrated college English teaching system based on OBE backward design. It establishes four categories of bilingual learning resources and a three-level assessment system encompassing process, outcome and developmental evaluation, with an aerospace-themed unit for law majors adopted as a practical teaching case. The framework focused in this paper improves students’ cultural reserves and cross-cultural narrative competence. Restricted by single-discipline samples, the model needs further multi-major trials for wider application.